2021
DOI: 10.1039/d0fo02711a
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin protects mouse ovarian granulosa cells from injury induced by the toxin zearalenone

Abstract: This study investigated the protective effect of scutellarin on ZEA-induced reproductive toxicity both in vivo and in vitro and explored the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…elegans ced-3 homologues) in vitro . , ZEN has been also demonstrated to trigger apoptosis through the activation of caspase 9 and caspase 3 protein expression and the cleavage of poly (ADP-ribose) polymerase (PARP) in mammalian Leydig cells and different tissues in vivo . These are consistent with our results (Figure ). Other tissue or cell culture studies have found that the ZEN-induced apoptosis and cell death were via caspase 3 activation and associated with the mitochondrial signaling pathway based on the protein level analysis. , Similarly, our study also revealed that the activated apoptosis and mitochondrial fission pathway probably resulted from mitochondrial dysfunction by ZEN exposure (Figures and ).…”
Section: Resultsmentioning
confidence: 90%
“…elegans ced-3 homologues) in vitro . , ZEN has been also demonstrated to trigger apoptosis through the activation of caspase 9 and caspase 3 protein expression and the cleavage of poly (ADP-ribose) polymerase (PARP) in mammalian Leydig cells and different tissues in vivo . These are consistent with our results (Figure ). Other tissue or cell culture studies have found that the ZEN-induced apoptosis and cell death were via caspase 3 activation and associated with the mitochondrial signaling pathway based on the protein level analysis. , Similarly, our study also revealed that the activated apoptosis and mitochondrial fission pathway probably resulted from mitochondrial dysfunction by ZEN exposure (Figures and ).…”
Section: Resultsmentioning
confidence: 90%
“…177 In addition, it was also reported in female Kunming mice that baicalein affected cell cycle distribution and apoptosis through the mitochondrial apoptosis pathway Food & Function Review and could target mouse ovarian granulosa cells to attenuate ZEN-induced reproductive toxicity. 178 It has been reported that silymarin has protective effects on the liver and can provide beneficial protection against ZEN-induced reproductive toxicity by improving antioxidant capacity and regulating genes related to protein synthesis, ZEN metabolism, hormone synthesis, and ABC transporters. 32 These results can be attributed to the antioxidant and estrogenic effects of silymarin.…”
Section: Flavonoidsmentioning
confidence: 99%
“…© 2022 The Authors. Food Frontiers published by NCU, NWU, JSU, ZJU & FAFU and John Wiley & Sons Australia, Ltd. Higazy et al, 2021;Li et al, 2021b;Ngolong Ngea et al, 2020;Rushing & Selim, 2019;Wei et al, 2020a;Yang et al, 2018;Yi et al, 2021;Zhang et al, 2020a). Mycotoxins can cause disease including cancer (Wu et al, 2021bc), neural tube defects (Sheik Abdul & Marnewick, 2020), chronic tubulointerstitial kidney (Tao et al, 2018), and cardiovascular diseases (Li et al, 2020a) and lead to huge economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Common mycotoxins in these foods include aflatoxin B1 (AFB1), aflatoxin M1 (AFM1), fumonisin B1 (FB1), ochratoxin A (OTA), zearalenone (ZEN), patulin (PAT), and T‐2 toxin (Deng et al., 2021; Hanvi et al., 2021; Iqbal et al., 2021; Li et al., 2021a; Ndaw et al., 2021; Zhang et al., 2021). Mycotoxins can be genotoxic, neurotoxic, nephrotoxic, cytotoxic and can have reproductive toxicity (Ezdini et al., 2020; Higazy et al., 2021; Li et al., 2021b; Ngolong Ngea et al., 2020; Rushing & Selim, 2019; Wei et al., 2020a; Yang et al., 2018; Yi et al., 2021; Zhang et al., 2020a). Mycotoxins can cause disease including cancer (Wu et al., 2021bc), neural tube defects (Sheik Abdul & Marnewick, 2020), chronic tubulointerstitial kidney (Tao et al., 2018), and cardiovascular diseases (Li et al., 2020a) and lead to huge economic losses.…”
Section: Introductionmentioning
confidence: 99%